2019
DOI: 10.1080/21645515.2019.1667206
|View full text |Cite
|
Sign up to set email alerts
|

Unique product quality considerations in vaccine development, registration and new program implementation in Malaysia

Abstract: This review aims to present the unique considerations for manufacturing and the regulation of new vaccines in Muslim-populated countries such as Malaysia. Our specific objectives are to highlight vaccine production and the ingredients of concern, summarize the current mechanism for ruling and recommendations on new vaccines, outline the different steps in decision-making on incorporating a new vaccine into the National Immunization Program, describe its issues and challenges, and explore the commercial viabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 25 publications
0
29
1
1
Order By: Relevance
“…A recent study conducted in Malaysia on vaccine development showed their willingness towards trusting ‘halal’ vaccines. Malay Muslim children’s parents have expressed concerns regarding the vaccine ingredients’ halal state because they believe that imported vaccines might be composed of porcine-derived agents, such as deoxyribonucleic acid (DNA), which is not halal, as the utilization of porcine-sourced products, including medicines, is generally not permissible for Muslims [ 36 ]. For vaccination against SARS-CoV-2, similar concerns arose in Indonesia [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted in Malaysia on vaccine development showed their willingness towards trusting ‘halal’ vaccines. Malay Muslim children’s parents have expressed concerns regarding the vaccine ingredients’ halal state because they believe that imported vaccines might be composed of porcine-derived agents, such as deoxyribonucleic acid (DNA), which is not halal, as the utilization of porcine-sourced products, including medicines, is generally not permissible for Muslims [ 36 ]. For vaccination against SARS-CoV-2, similar concerns arose in Indonesia [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, more qualitative studies are required in the African setting to decipher and address possible causes of COVID-19 vaccine hesitancy [ 23 ]. It is worth noting that in Somalia as in other Muslim nations, the ‘halal’ nature of any vaccine is of prime importance [ 24 ]. This explains why concerns were raised regarding the use of porcine derivatives when manufacturing COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, recently an Iranian cleric urged public not to get COVID-19 vaccine as it could possibly make people homosexual [9]. Similarly, in Malaysia and Indonesia, public raised a great hue and cry against COVID-19 vaccination drive based on a piece of misinformation that "the vaccine is Haram as it contains pork gelatin" [10] . In line with this, Islamic clerics in UAE and India passed a religious decree against COVID-19 vaccine that adversely affected the uptake of the vaccine in the Muslim communities.…”
Section: Vaccine Hesitancy Based On Misinformation Disinformation and Conspiracy Theoriesmentioning
confidence: 99%